Leisure and Free Time Practices of Working-Class Women in Lima - Luque Velarde, Martha (2025)
This article examines the leisure and free time practices of working-class women in Lima, relating to recreation and rest developed in the interstices of domestic work and informal work domains. To this end, a typology of leisure and free time is elaborated considering the following categories: personalized, with family, altruistic and cooperative, and market-based. It is established that self-sufficiency, family, and reciprocity practices predominate, going beyond market relations and allowing the construction of equal relationships among women, while market-based leisure and free time corresponds to a reduced aspect of female life involving capital actions. The study was conducted through a probabilistic survey applied in human settlements.